Drivers of police agencies’ resistance to body-worn camera adoption - Andreescu, Viviana (International journal of police science & management, 2022)
Although the use of video-recording technology in policing is on the rise in the United States, not all police agencies in the country are following this trend. Using Law Enforcement Management and Administrative Statistics Body-Worn Camera Supplement survey data collected in 2016 from a nationally representative sample of general-purpose law enforcement agencies, the present analysis identified some of the factors more likely to predict interagency differences in the intention to adopt body-worn cameras (BWCs). Findings show that resistance to the adoption of BWCs is reported by law enforcement agencies that do not think the new technology is needed, report a lack of support for BWC adoption from the agency's leadership and from patrol officers, and have privacy and cost-related concerns. Although the perceived lack of public support for the adoption of BWCs does not differentiate agencies that intend to acquire BWCs from agencies that do not, police departments that registered a higher percentage of complaints for excessive use of physical force are significantly more likely to oppose the adoption of BWCs. Support for BWC adoption is significantly higher in police departments that have acquired other types of recording equipment in the past. Even though recent state-level legislative changes related to BWCs do not have a significant impact on BWC adoption decisions at the organization level, results indicate that law enforcement agencies located in US states with strong police unions are more likely to show resistance to the adoption of BWCs in the near future.